Minsky crisis - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
Stability is destabilizing. These three words concisely capture the insight that underlies Hyman Minsky's analysis of the economy's transformation over the entire postwar period. The basic thesis is that the dynamic forces of a capitalist economy are explosive and must be contained by institutional ceilings and floors. However, to the extent that these constraints achieve some semblance of stability, they will change behavior in such a way that the ceiling will be breached in an unsustainable speculative boom. If the inevitable crash is cushioned by the institutional floors, the risky behavior that caused the boom will be rewarded. Another boom will build, and the crash that follows will again test the safety net. Over time, the crises become increasingly frequent and severe, until finally it (a great depression with a debt deflation) becomes possible. Policy must adapt as the economy is transformed. The problem with the stabilizing institutions that were put in place in the early postwar period is that they no longer served the economy well by the 1980s. Further, they had been purposely degraded and even in some cases dismantled, often in the erroneous belief that free markets are self-regulating. Hence, the economy evolved over the postwar period in a manner that made it much more fragile. Minsky continually formulated and advocated policy to deal with these new developments. Unfortunately, his warnings were largely ignored by the profession and by policymakers - until it was too late.
Keywords: B22; B25; B26; B52; E02; E11; E12; E44; G01; O11; 330; stability is destabilizing; Hyman Minsky; money manager capitalism; financial instability hypothesis; global financial crisis; self-regulating markets